An evaluation of percentile measures of citation impact, and a proposal for making them better - Bornmann, Lutz; Williams, Richard (Scientometrics, 2020)
Percentiles are statistics pointing to the standing of a paper’s citation impact relative to other papers in a given citation distribution. Percentile Ranks ( PR s) often play an important role in evaluating the impact of researchers, institutions, and similar lines of study. Because PR s are so important for the assessment of scholarly impact, and because citations differ greatly across time and fields, various percentile approaches have been proposed to time- and field-normalize citations. Unfortunately, current popular methods often face significant problems in time- and field-normalization, including when papers are assigned to multiple fields or have been published by more than one unit (e.g., researchers or countries). They also face problems for estimating citation counts for pre-defined PR s (e.g., the 90th PR ). We offer a series of guidelines and procedures that, we argue, address these problems and others and provide a superior means to make the use of percentile methods more accurate and informative. In particular, we introduce two approaches, CP - IN and CP - EX , that should be preferred in bibliometric studies because they consider the complete citation distribution and can be accurately interpreted. Both approaches are based on cumulative frequencies in percentages ( CP s). The paper further shows how bar graphs and beamplots can present PR s in a more meaningful and accurate manner.